If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(6m + -2) = 0 Reorder the terms: 6(-2 + 6m) = 0 (-2 * 6 + 6m * 6) = 0 (-12 + 36m) = 0 Solving -12 + 36m = 0 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 36m = 0 + 12 Combine like terms: -12 + 12 = 0 0 + 36m = 0 + 12 36m = 0 + 12 Combine like terms: 0 + 12 = 12 36m = 12 Divide each side by '36'. m = 0.3333333333 Simplifying m = 0.3333333333
| y/4+5=-16 | | 6(2x-1)-2(2x)=6 | | 3-2y+3= | | p^2+12p+40=8 | | x/5-6=0 | | 9-10x=161-38x | | 3x+35=12x-32 | | 8-(-10/3) | | 5x^2-21+22=0 | | 6x+68+12x=24 | | 5/9x+6/9=8/9 | | (x+8)(x+8)=-81 | | 5/6*-4 | | r-3s-3t-4r+10s+8t=0 | | k^2=3k-2 | | 9x-51=5x+21 | | 3m+14=4m | | 1/4/6/7 | | 4X+3-2X=15-5U-11 | | 7x-61=-4x+71 | | 8x-66=-2x+74 | | v^2+v-53=3 | | 5(4x-4)+1=20x-19 | | -23-4x=-9x+56 | | 1-7(-1/-2) | | 2m-9n-5m+4n=0 | | 700=100+4Q | | -43+7x=29+x | | 6-(-54/7) | | 17+b=25 | | 6/7*-9 | | 16+3x= |